Effect Of Composite Flour Ratios (Rice Flour, Tapioca, Cornstarch, And Almond Powder) On The Sensory And Physical Quality Of Scones - Naurah Qurratul Islam; Ridawati Ridawati; Mutiara Dahlia (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study analysed the effect of composite flour ratios consisting of white rice flour, tapioca, cornstarch, and almond powder on the sensory and physical quality of scones. Three wheat-free formulations were prepared at ratios of 2:1:1:1, 2:1:1:2, and 2:1:1:3, while a wheat-flour formulation was retained as the physical-quality control. The experimental study involved five expert validators and 45 semi-trained panelists. Sensory attributes included top colour, side colour, aroma, taste, outer texture, and inner texture. Physical quality was evaluated through bake loss and expansion, each measured in three replications. Sensory data were analysed using the Kruskal–Wallis test, while physical data were examined using one-way ANOVA followed by Duncan’s Multiple Range Test when a significant effect was detected. The three composite-flour ratios did not significantly affect any sensory attribute because all calculated Kruskal–Wallis values were below the critical value of 5.991. Nevertheless, the 2:1:1:2 formulation produced the highest descriptive scores for top colour (4.8) and taste (4.1), while maintaining favourable aroma and texture. Composite flour ratio significantly affected bake loss (F = 10.177 > Fcritical = 4.066), with means of 10.39%, 10.26%, and 9.97% for the three treatments, respectively. Expansion did not differ significantly (F = 0.452 < Fcritical = 4.066), with corresponding means of 9.84%, 9.73%, and 9.26%. Overall, the 2:1:1:2 ratio was recommended because it combined the strongest sensory acceptance with acceptable physical performance. The results demonstrate that a balanced composite-flour system can produce acceptable wheat-free scones while increasing the use of alternative flour ingredients.